Avaliação do potencial fitorremediador de plantas floríferas em solo contaminado com cobre - Menegaes, Janine Farias (2015)
Soil contamination is an environmental, social and economic problem. In wine areas, prolonged use of phytosanitary products, the copper base, contributed to the accumulation of this element in the soil, when in excess is highly damaging to the development of plants, impacting on their productive potential. In order to minimize the harmful effect of Cu in soils of these areas, this study aimed to evaluate the cultivation and the potential extraction of this element in three floricultural species: calla lily (Zantedeschia spp.), dianthus (Dianthus chinensis L.) and chrysanthemum (Dendranthema grandiflora Tzevelev), to play the role phytoremediation in soil, seeking a low environmental impact agriculture. Three separate experiments were carried out from October 2013 to December 2014, in a protected environment in the Floriculture sector in UFSM, Santa Maria, RS. The soil was collected in areas of viticulture. And, the contents of Cu added were in the ground by means of copper sulphate. In Chapter I evaluated the development and the water consumption of calla lily under different irrigation strategies and copper levels in the soil. The trial was in DIC (completely randomized design), with factorial arrangement 4x3 (four copper levels and three irrigation strategies), with five repetitions. It was found that these levels of added Cu in soil does not interfere with the daily water consumption calla lily, obtaining average daily 0.5, 0.8 and 1.2 mm day-1 for the blades 40, 60 and 80% CRA (water retention capacity of the vessel), respectively, and that this species is tolerant crop in this environment. In Chapter II evaluated the development and the water consumption of dianthus and its effect on the culture in ground presenting excess Cu. The test was DIC in factorial 4x3 (four copper levels and three irrigation strategies), with five repetitions. It was found that Cu content added to the soil will not interfere with the daily water consumption dianthus obtaining daily averages 0.42; 0.72 and 0.91 mm day-1 for the blades 40, 60 and 80% CRA, respectively, and the results showed fitorremediativa fitness grapevine species to soils with excess of this metal. Chapter III evaluated the development of chrysanthemum cv. Dark Fiji grown in soil with excess Cu. The test was DIC in factorial 5x2 (five levels of added Cu in soil and two crop cycles), with five repetitions. It was found that the increase of Cu in the soil affect the normal development and growth of the culture, however, it showed tolerance to crop species in soil with excess Cu, accumulating high concentrations of this element in the roots. We conclude so, overall, the three species have tolerance culture in ground presenting excess Cu, highlighting the dianthus as promising phytoremediation soil.